Development of PVC membranes with clove oil as plasticizer for blood bag applications - Ahmed M. Omer, T. M. Tamer, Abd EL Monem, Sami Abd Elmoaty, Mona Abd El Fatah, Gamal R Saad (Journal of Applied Pharmaceutical Science, 2016)
In the present study, Antimicrobial PVC films containing different amounts of clove oil as a plasticizer were prepared using traditional casting method. The physical and mechanical properties of the plasticized PVC membranes e.g. surface wettability were investigated. The increase of clove oil content demonstrated an increase in surface hydrophilicity and elongation to break the film. The thermogravimetric analysis revealed a decrease of polymer thermal stability by increasing clove oil concentration. The antibacterial activities against four different bacterial strains (two-gram positive: Staphylococcus aureus and Bacillus cereus & two-gram negative: Pseudomonas aeruginosa and Escherichia coli) were promoted by addition of clove oil. Although the natural source of clove oil, the bio-evaluation of plasticized membranes showed an increase in hemolysis percent (%) and thrombus weight. It can be concluded that the addition of clove to PVC need to further studies for applying in blood bags.
Keywords: PVC, membranes, clove oil, plasticizer, antibacterial.